2010
DOI: 10.1016/j.ejcts.2010.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricle-to-pulmonary artery shunt related complications after Norwood procedure☆

Abstract: The RV-PA shunt can be a safe and efficient technique in providing optimal pulmonary blood flow in the children with HLHS after Norwood procedure, performed with minimal rate of complications. In our experience, the use of RV-PA shunt in NP does not require earlier second-stage procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…Potential explanations for differences in branch pulmonary artery growth patterns include anatomical abnormalities with the shunt or branch pulmonary arteries(16) and hemodynamic factors such as shunt diameter(12), as well as pulsatile versus non-pulsatile shunt blood flow(11). In contrast to our findings of inferior pulmonary artery growth in the RVPAS cohort, Januszewska and colleagues(17) reported that despite RVPAS subjects’ having a significantly lower Qp:Qs (0.8 vs. 1.2), lower aortic oxygen saturation (67.4% vs. 75.3%), and lower SVC oxygen saturation (43.5% vs. 49.7%), they had good, symmetric pulmonary artery growth prior to the stage II procedure. One purported advantage of the RVPAS is that it allows pulsatile flow into the branch pulmonary arteries, which may improve interstage pulmonary artery growth, as compared with the MBTS, which provides continuous flow.…”
Section: Discussioncontrasting
confidence: 99%
“…Potential explanations for differences in branch pulmonary artery growth patterns include anatomical abnormalities with the shunt or branch pulmonary arteries(16) and hemodynamic factors such as shunt diameter(12), as well as pulsatile versus non-pulsatile shunt blood flow(11). In contrast to our findings of inferior pulmonary artery growth in the RVPAS cohort, Januszewska and colleagues(17) reported that despite RVPAS subjects’ having a significantly lower Qp:Qs (0.8 vs. 1.2), lower aortic oxygen saturation (67.4% vs. 75.3%), and lower SVC oxygen saturation (43.5% vs. 49.7%), they had good, symmetric pulmonary artery growth prior to the stage II procedure. One purported advantage of the RVPAS is that it allows pulsatile flow into the branch pulmonary arteries, which may improve interstage pulmonary artery growth, as compared with the MBTS, which provides continuous flow.…”
Section: Discussioncontrasting
confidence: 99%
“…Following a ventriculotomy, a conduit is inserted between the RV and the main pulmonary artery. This results in volume loading from conduit regurgitation and a scar on the systemic ventricle predisposing the patient to an increased risk of arrhythmias or aneurysmal dilatation of the outflow tract [5]. Recent evidence from a large randomized trial initially showed no differences in echocardiographic measures of RV ejection fraction (EF) at 1 year of age [6].…”
Section: Introductionmentioning
confidence: 99%
“…Shunt stenosis at the proximal end, a frequently reported complication of the RV‐PA shunt, cannot be dealt with in this approach. To prevent proximal stenosis, the whole wall myocardium at the ventriculotomy is removed with the coronary punch bioptome, and a large‐diameter anastomosis is created using a 6 mm conduit in patients weighing more than 2,800 g.…”
Section: Discussionmentioning
confidence: 99%